(untitled) (Revista de Investigaciones Universidad del Quindío, 2019)
Given the importance that foreign direct investment has been acquiring in the countries, this research aimed to find the determining factors of Foreign Direct Investment that enters Colombia in the period between 2000-2018, through the series econometric analysis. In the free distribution software Gretl, whose results showed that despite the fact that the unemployment rate and the interest rate are the factors that most influence the attraction of this type of investment to the country, it is the international dynamics that contribute to that the transnational companies are located in Colombia and there is no real capacity to attract them, for which a change of economic structure is required.